The Cambridge aerospace dictionary - Gunston, Bill (Cambridge aerospace series., 2004)
'The Cambridge Aerospace Dictionary' offers coverage of terminology used throughout the aerospace industry, including materials & aerospace organizations. This new dictionary includes over 15,000 new terms, mostly acronyms.